The Popular Front in Europe
VII, 171 p.
Keywords: Out of the social and economic turmoil of Europe in the 1930s, the Popular Front emerged as the spearhead of the left's bid to stop fascism in its tracks. Fifty years on from the birth of the Popular Front this edited collection assesses the impact of the idea of bourgeois-proletarian alliance on the European left as a whole. It also examines the fate of the Popular Front governments, both in France, which remained nominally 'at peace', and in Spain, where the bitter strife over social and economic reform erupted into open civil war.